The painted drum - Erdrich, Louise (New York, NY Harper Collins Publishers, 2005)
Discovering a cache of valuable Native American artifacts while appraising an estate in New Hampshire, Faye Travers investigates the history of a ceremonial drum, which possesses spiritual powers and changes the lives of people who encounter it.
"Advance reader's edition not for sale"--Cover.
Minnesota Book Award, 2006.
111104
Keywords: Indians of North America -- Fiction; Indian reservations -- Fiction; Villages; Psychological fiction; New England -- Fiction; Domestic fiction; Fiction